Apexification of nonvital immature mandibular premolars using two different techniques - Ping-Han Wen; Ji-Uei Liou; Bor-Ren Duh (Elsevier, 2009)
The purpose of this report was to present two cases of mandibular premolars with necrotic pulp and open apices treated with two different techniques. The first case was a 20-year-old female whose teeth 35 and 45 were diagnosed with pulpal necrosis and chronic apical periodontitis, possibly resulting from dens evaginatus. Traditional apexification with Ca(OH)2 was chosen; however, teeth 35 and 45 fractured after 2 and 9 months, respectively. The second case was an 11-year-old boy whose tooth 45 was diagnosed with necrotic pulp and a chronic apical abscess, possibly resulting from dens evaginatus. The mineral trioxide aggregate (MTA) barrier technique was performed after short-term Ca(OH)2 dressing, and the remaining space of the canal was filled with light-cured composite resin. The tooth remained healthy and functional at 1-year follow-up. The apical barrier technique using MTA has the advantages of a reduced treatment time, lower chance of tooth fracture, and fewer visits to the dental office. This report demonstrates that the MTA barrier technique followed by light-cured composite resin filling can be a good alternative treatment to traditional apexification.